2017
DOI: 10.1002/2016jc012022
|View full text |Cite
|
Sign up to set email alerts
|

Subtidal circulation in a deep‐silled fjord: Douglas Channel, British Columbia

Abstract: Douglas Channel, a deep fjord on the west coast of British Columbia, Canada, is the main waterway in the fjord system that connects the town of Kitimat to Queen Charlotte Sound and Hecate Strait. A 200 m depth sill divides Douglas Channel into an outer and an inner basin. This study examines the low‐frequency (from seasonal to meteorological bands) circulation in Douglas Channel from data collected at three moorings deployed during 2013–2015. The deep flows are dominated by a yearly renewal that takes place fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(44 citation statements)
references
References 29 publications
7
37
0
Order By: Relevance
“…The net volume transport in the Douglas Channel is up‐fjord and about 19,000 m 3 /s. This value is consistent with the observation‐based estimates of net up‐fjord transport (Wan et al, ). The net volume transport in the Devastation Channel is inward into the triple junction and about 18,900 m 3 /s, indicating that the inward transport in the subsurface layer is larger than the outward transport in the surface layer.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The net volume transport in the Douglas Channel is up‐fjord and about 19,000 m 3 /s. This value is consistent with the observation‐based estimates of net up‐fjord transport (Wan et al, ). The net volume transport in the Devastation Channel is inward into the triple junction and about 18,900 m 3 /s, indicating that the inward transport in the subsurface layer is larger than the outward transport in the surface layer.…”
Section: Resultsmentioning
confidence: 99%
“…Wind‐driven currents often dominate the near‐surface flow in fjords (e.g., Alberni Inlet, Farmer & Osborn, ; Knight Inlet, Baker & Pond, ). Recent observations (Wan et al, ) show that indeed wind can reverse the down‐fjord surface estuarine flow during strong wind events in the Douglas Channel.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This strong stratification can result in increased wind influence on surface currents (Thomson, ). Wan et al () investigated the near‐surface currents and found that 60%–70% of the subtidal variance in the currents could be explained by a linear regression against wind speed. The wind‐driven flow ( 5% of the wind speed) is superimposed on an estuarine surface outflow of 14–23 cm s 1.…”
Section: Observationsmentioning
confidence: 99%